Soft System Methodology Framework for Fair and Balanced of Risk and Value-Added Distribution in Sugarcane Agroindustry Supply Chains - Asrol, Muhammad; a, Marimin; a, Machfud; Yani, Moh. (International Journal of Supply Chain Management, 2018)
Fair risk and value-added distribution within sugarcane agroindustry supply chain stakeholder is a complex and unstructured problem which had to be solved comprehensively. This research proposed a fair and balanced risk and value-added distribution model using Soft System Methodology (SSM) framework combined with negotiation system and Fuzzy Cognitive Maps (FCM) technique. SSM is a powerful approach to identify and solve a complex and unstructured problems then recommend effective solutions. Negotiation system was modelled to operate a fair and balanced risk and value-added distribution to achieve sugarcane supply chains goals. FCM was applied to validate the conceptual model and deliver system improvements. This research succeeded to describe and structure the sugarcane supply chains problems and deliver to conceptual and quantitative solution. Fair and balanced of risk and value-added distribution model with collaboration and negotiation mechanism hadbeenformulated at fourth stage of SSM. This research also proposed a negotiation system with quantitative intelligent model to operate the supply chains collaboration. Framework for system validation and recommendation hadbeenformulated through FCM at fifth and sixth stages of SSM. For further research, this framework required to be validated with more experienced expert then applied at real cases.